2023
DOI: 10.1021/acs.macromol.3c00973
|View full text |Cite
|
Sign up to set email alerts
|

Seeded Epitaxial Growth of Crystallizable Polymers Governed by Crystallization Temperatures

Abstract: Seeded growth is generally regarded as an ambient-temperature, living crystallization-driven self-assembly (CDSA) approach of block copolymers (BCPs) with crystallizable cores, which is a powerful method in preparing one-dimensional (1D) or twodimensional (2D) polymer nanomaterials with precise control over size and compositions. Generally, crystallographic matching is considered as a fundamental principle that determines the happening of epitaxial growth. However, crystallization temperature also plays a vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…When a mixed solution of PCL-G and PHL-R is added to 2D PHL platelet simultaneously at 25 °C, CLSM analysis reveals that only PHL component can deposit among the PHL platelet, while the PCL component tends to form larger platelets that are formed by the self-nucleation of PCL (Figure B, 25 °C). This result shows that PCL can not heteroepitaxially grow from the PHL crystal domains at 25 °C, which is in consistent with our previous results. , However, when the temperature decreases to 4 °C, both PCL and PHL components could grow from the PHL core-forming platelets, yielding concentric platelets, although the composition distribution is heterogeneous (Figure B, °C). On the other hand, after addition of a mixture of POL-R and PCL-G simultaneously to 2D PHL platelet at 25 °C, an interesting phenomenon is observed (Figure C, 25 °C).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…When a mixed solution of PCL-G and PHL-R is added to 2D PHL platelet simultaneously at 25 °C, CLSM analysis reveals that only PHL component can deposit among the PHL platelet, while the PCL component tends to form larger platelets that are formed by the self-nucleation of PCL (Figure B, 25 °C). This result shows that PCL can not heteroepitaxially grow from the PHL crystal domains at 25 °C, which is in consistent with our previous results. , However, when the temperature decreases to 4 °C, both PCL and PHL components could grow from the PHL core-forming platelets, yielding concentric platelets, although the composition distribution is heterogeneous (Figure B, °C). On the other hand, after addition of a mixture of POL-R and PCL-G simultaneously to 2D PHL platelet at 25 °C, an interesting phenomenon is observed (Figure C, 25 °C).…”
supporting
confidence: 92%
“…One-dimensional (1D) or two-dimensional (2D) nanoparticles with precision control over size can be obtained via a process of crystallization-driven self-assembly (CDSA) of block copolymers. Seeded growth termed “living” CDSA has been identified as a powerful method to create size-tunable nanoparticles that could be regulated by mass ratios of unimer-to-seed. The precise control of 1D or 2D micelles using the seeded growth approach with an identical crystallizable core is extensively studied, and a range of well-defined core–shell nanoparticles are created. Epitaxial crystallization is usually regarded as the crystal growth mechanism for the formation of uniform micelles. These uniform core–shell micelles represent an attractive category of nanomaterials due to their widespread applications in terms of sensors, , catalyst, reinforcement, , and emulsion. , …”
mentioning
confidence: 99%
“…Instead, polydisperse platelets formed from spontaneous nucleation were observed (Figure S21), implying that the growth was hindered at this temperature (20 °C). Our recent report on the formation of 2D platelet block comicelles with compositionally distinct cores verified that crystallization temperature was a critical parameter for successful heteroepitaxial growth. , On the basis of this vital factor, we therefore performed seeded growth at low crystallization temperatures. Taking the seeded growth of P6C 26 /P6C 26 - b -PDMA 272 from 1D PCL-based seeds as an example, the seeded growth morphologies were examined at different crystallization temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, understanding the seeded growth process from the perspective of polymer crystallization is vital, as it would enable the preparation of a wide range of segmented micelles with diverse cores. For example, our previous reports have shown that crystallization kinetics is a key factor to regulate the epitaxial growth of polymer A from seed crystal B . , Low crystallization temperatures are beneficial for the effective epitaxial growth, and the factor of thinner epitaxial crystals ( A ) than those of the substrate ( B ) governs the occurrence of epitaxial growth …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the important effect of secondary nucleation upon epitaxial crystallization between polymers was also highlighted . Very recently, Tong and co-workers have approved that lattice matching is indeed required but insufficient for successful epitaxy and the critical nuclei size dominates the epitaxial growth. , Despite the extensive studies with diverse systems over the past decades, regulating polymer crystallization via epitaxy is nowadays hardly desirable. ,, More importantly, due to the very short range of interfacial epitaxial interaction, the past works involve polymer epitaxy focused on very thin films with the main evidence of crystal morphologies and orientation relationships obtained by atomic force microscopy, transmission electron microscopy, and electron diffraction, , while polymer epitaxy from bulk crystallization is seldom concerned and the featured evidence is essentially missing . Meanwhile, a molecular-level comprehension of the epitaxial mechanism remains controversial and is still far from conclusive. , ,, Therefore, understanding and controlling polymer crystallization via epitaxy especially in bulk materials on foreign surfaces have been and remain to be a serious challenge in polymer physics. , …”
Section: Introductionmentioning
confidence: 99%